1996
DOI: 10.1177/014662169602000106
|View full text |Cite
|
Sign up to set email alerts
|

Are Simple Gain Scores Obsolete?

Abstract: It is widely believed that measures of gain, growth, or change, expressed as simple differences between pretest and posttest scores, are inherently unreliable. It is also believed that gain scores lack predictive validity with respect to other criteria. However, these conclusions are based on misleading assumptions about the values of parameters in familiar equations in classical test theory. The present paper examines modified equations for the validity and reliability of difference scores that describe appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 23 publications
2
102
0
Order By: Relevance
“…Prior to conducting the analyses examining potential determinants of satisfaction, change scores were computed to represent change in clinical outcomes from baseline to six-month follow-up by subtracting the six-month follow-up score from the baseline score for each measure. Although there is controversy regarding the use of change scores (also known as simple gain scores), there is support for use of this method for this purpose (Williams & Zimmerman, 1996;Zimmerman & Williams, 1998) and they have been used in well established evaluations of outcomes in children's mental health services .…”
Section: Discussionmentioning
confidence: 99%
“…Prior to conducting the analyses examining potential determinants of satisfaction, change scores were computed to represent change in clinical outcomes from baseline to six-month follow-up by subtracting the six-month follow-up score from the baseline score for each measure. Although there is controversy regarding the use of change scores (also known as simple gain scores), there is support for use of this method for this purpose (Williams & Zimmerman, 1996;Zimmerman & Williams, 1998) and they have been used in well established evaluations of outcomes in children's mental health services .…”
Section: Discussionmentioning
confidence: 99%
“…It is not directly measured and thus modeled as a latent variable with measurement errors of Y estimated. Albeit a full discussion of this approach of modeling change is beyond the scope of the present study, it should be noted that, although this method was once criticized, for example, by Lord (1956) as unreliable, later work has shown that the criticisms are not necessarily valid (Rogosa & Willett, 1983;Williams & Zimmerman, 1996). Indeed, recent work in psychology (McArdle, 2009), biology (Fitzmaurice, 2001), economics (Wooldridge, 2002), sociology (Halaby, 2004), and education (Willett, 1988) has recognized the appreciable reliability, validity, and usefulness of the change score approach.…”
Section: An Lcs Approach To Studying Dynamic Reciprocal Relationshipsmentioning
confidence: 93%
“…In classical test theory, the additional assumptions σ X = σ Y and ρ XX 0 ¼ ρ YY 0 can sometimes be made, although there are cases in which these assumptions are clearly inappropriate (Williams & Zimmerman, 1996). Within RT research, it seems reasonable that both of these assumptions would be true to a good approximation, because differences are usually computed between mean RTs obtained using very similar conditions.…”
Section: Person K and Parametermentioning
confidence: 99%